PERTIMBANGAN HAKIM DALAM PENETAPAN PERMOHONAN DISPENSASI KAWIN SEBAGAI UPAYA MENUTUP MALU AKIBAT HAMIL DI LUAR NIKAH (Studi Putusan Pengadilan Agama Kelas 1B Sengkang Nomor 1/Pdt.P/2020/PA.Skg. Perspektif Hukum Islam) - Iffah Annisa Faulia Gusti Hasan; Hartini Tahir; Musyfikah Ilyas (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2022)
This research discusses how the Judge's Consideration of the Application for Marriage Dispensation as an Effort to Cover Shame due to Pregnancy Out of Wedlock (Study of the Decision of the Sengkang Class 1B Religious Court Number 1/Pdt.P/2020/PA.Skg Perspective of Islamic Law)". From the main problem, the writer formulates several sub-problems, namely: What is the process of applying for a marriage dispensation at the Sengkang religious court? What are the positive and negative aspects in the provision of marriage dispensation due to pregnancy out of wedlock? and How is the judge's consideration in granting a marriage dispensation case due to pregnancy out of wedlock on case number 1/Pdt.P/2020/PA.Skg Perspective of Islamic Law? This type of research is field research or can be called qualitative research, field research is carried out using the method of observation, interviews, and describes the facts that occur in the field. The results of this study indicate that in granting the application for dispensation for marriage due to pregnancy out of wedlock, the Panel of Judges certainly bases its considerations on the principles of Islamic law, one of which is that if it is linked between taking benefit or rejecting harm, then rejecting harm takes precedence over taking benefit. The implication of this research is that parents should pay more attention to their children so that unwanted things do not happen. And people should be more aware and understand the laws that apply in this country in order to realize a happy and prosperous marriage. Keywords: Dispensation for Marriage, Pregnant Out of Wedlock, Islamic Law.